PERENCANAAN APLIKASI PENGENALAN HASIL PERTANIAN PADA MASYARAKAT KELOMPOK TANI DESA COMPONG KABUPATEN SIDRAP - Hamra, Hamra; Sahiddin, Sudirman; Evi AS, Nur (Jurnal Sintaks Logika, 2021)
Farming is a profession that produces food. Farmers generally cultivate the land with the aim of growing and maintaining crops such as rice, fruit, tubers, and so on. usually produce from agriculture for their own consumption or sale. Farmers usually sell their agricultural products to collectors, then the collectors sell the agricultural products to the shop, then the shop will sell it to the community. Application planning for the introduction of agricultural products to the community of farmer groups in the village of Compong Kab. The sidrap made can provide marketing media to farmers, where farmers can introduce their agricultural products to the community through applications. So that the farmers will easily introduce their agricultural products to the community. Where this application can be accessed by the community easily, the community can also find out the results, information about agricultural products from the village of Compong. Create applications using the PHP language program, and JavaScript. In its use, planning applications for the introduction of agricultural products to the community of farmer groups in the village of compong, kab. sidrap utilizes internet communication lines. The application can be used easily when you want to input agricultural data.